Exploring Emirati EL teachers' beliefs about teaching and their relationship to classroom practices: a hermeneutic study - Valenzuela, Jacqueline Soledad (2014)
Research shows that teacher beliefs are central to understanding teacher behaviour. Studying teacher beliefs is crucial to understand and affect their practices. Research also shows that classroom practices are influenced and determined by contextual factors in the teaching environment. Hence, teacher beliefs and contextual circumstances influence teachers’ instructional choices and decisions, revealing a relationship between teacher beliefs and contextual factors as variables affecting teaching practices. This study explores female Emirati teachers’ beliefs about teaching and their contextual environment, examining the way in which they relate to classroom practices. The study focused on English language teachers in secondary schools in the Emirates of Dubai and Sharjah, United Arab Emirates. To approach this research inquiry, a qualitative paradigm based on Gadamerian hermeneutics was adopted. The data-gathering process consisted of semi-structured interviews and classroom observations. Eight teachers participated in this study for a period of eight months. The data were analyzed using a meaning-based interpretive approach that sought understanding at idiographic and nomothetic levels. The findings showed the predominance of a salient mother-sister image that described how the teachers viewed themselves and concurrently provided a lens to look into their professional world. Their understanding of the nature of teaching rested, rather than on notions of subject matter and methodologies, on the student-teacher relationship which was viewed as an integral part of the teaching-learning process. The holistic view of student development evidenced a strong emphasis on student social skills and values. Their classroom practices generally reflected consistency with teacher beliefs, although points of discrepancy were also found. Similarly, lack of student academic motivation and negative attitude towards English were identified as the most prevalent contextual factors affecting teaching practices. The nature of these teachers’ beliefs and perceived contextual factors and their relationship to teaching practices are discussed as well as the implications, limitations and recommendations for further research.